ORIGINAL RESEARCH ARTICLE: HISTOPATHOLOGICAL EVALUATION OF ENDOMETRIAL BIOPSIES IN WOMEN WITH GYNECOLOGICAL COMPLAINTS - BHUVA, KAUSHIK; VACHHANI, ANAND; SAVJIANI, NISARG (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objectives of the study were to study histopathological evaluation of endometrial biopsies in women with gynecological complaints. Methods: The present study included 100 patients who attended gynecology department of Dhiraj General Hospital, SBKS MI and RC with the complaints of abnormal uterine bleeding. Endometrial biopsy or curettage done by clinician as part of diagnosis and management. Samples sent to the department of pathology for histopathological evaluation. Tissue after appropriate fixation and processing was embedded in paraffin block. After that, 4 micron tissue sections were cut and they were stained with H and E stain. The sections were evaluated on microscopy and an appropriate histopathological diagnosis was made. Results: Out of 100 cases studied, 37% were found out to be secretory endometrium, 20% proliferative endometrium, 6% disordered endometrial glands, 3% simple hyperplasia without atypia, 5% complex hyperplasia without atypia, 1% endometrial hyperplasia with atypia, 2% endometrial polyp, 7% chronic nonspecific endometritis, 1% tuberculous endometritis, 3% Arias-Stella reaction, 6% products of conception, 3% deciduitis, 1% complete hydatidiform mole, 2% endometrial carcinoma, and 3% squamous cell carcinoma of cervix. Conclusion: Abnormal uterine bleeding is a leading cause of morbidity in patients with gynecological complaints. It not just impairing health but psychologically also affects the patients. Endometrial biopsy is a safe, reliable, and less time-consuming outpatient procedure which can be used as an initial diagnostic tool in the patients with abnormal uterine bleeding.